An insight into the critical success factors influence on women entrepreneurship . - Mathushan, P.; Pushpanathan, A. (Faculty of Business Studies, Vavuniya Campus of the University of Jaffna., 2020)
Entrepreneurship has presently employed a prominent residence in the record of rewarding career opportunities for women. There is an extensive reservoir of human resource potential that remains untapped in the economy. Many factors influence women entrepreneurs when they are running their business. This study aims to identify the factors that influence the success of women entrepreneurs in the Northern Region. For this study purpose 100 small scale women entrepreneurs identified in the Northern Region registered in the Industrial Development Board. A convenient sampling technique was used in this study. Data is entered and analyzed using SPSS version 20. The present study results indicated that the mean square and F-value of the Economic factors, Socio-cultural factors, and Family factors significantly associate with the success of the women entrepreneurs. Further Correlation results indicated that Economic factors, Socio-cultural factors, and Family Factors are positively and significantly correlated with the success of women entrepreneurs and Psychological factors, Enterprise factors and legal factors are positively correlated but insignificant in this study.
Keywords: Critical Success Factors.; The Success of Women Entrepreneurs and Women Entrepreneurs.